2019
DOI: 10.17520/biods.2019101
|View full text |Cite
|
Sign up to set email alerts
|

Metabarcoding diet analysis of snow leopards (<i>Panthera uncia</i>) in Wolong National Nature Reserve, Sichuan Province

Abstract: As the apex predator of plateau ecosystems in Central Asia and the Qinghai-Tibet Plateau, the snow leopard (Panthera uncia) plays an essential role in maintaining food-web structure and ecosystem stability. Learning the diet composition and dynamics of the snow leopard is important for understanding its role in ecosystem functioning and interspecific interactions. Previous diet analyses of the snow leopard have been based mainly on morphological identification of food debris in the feces, though the accuracy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…With livestock occupying the space and food resources of blue sheep, their viability in the ecosystem decreases (Karimov et al 2018). Although some studies in recent years have shown that livestock make up an increasing proportion of the snow leopard's diet, the snow leopard's main food source is still blue sheep (Oli et al 1993;Bagchi and Mishra 2006;Lu et al 2019;Shehzad et al 2012). The availability of this prey is an important factor affecting the habitat selection of snow leopard (J.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With livestock occupying the space and food resources of blue sheep, their viability in the ecosystem decreases (Karimov et al 2018). Although some studies in recent years have shown that livestock make up an increasing proportion of the snow leopard's diet, the snow leopard's main food source is still blue sheep (Oli et al 1993;Bagchi and Mishra 2006;Lu et al 2019;Shehzad et al 2012). The availability of this prey is an important factor affecting the habitat selection of snow leopard (J.…”
Section: Discussionmentioning
confidence: 99%
“…Rare and threatened species that occur in the park include the snow leopard, giant panda, sambar deer (Rusa Unicolor), golden snub-nosed monkey (Rhinopithecus Roxellana) (Hou et al 2018;Shi et al 2017), gong tong (Davidia involucrata Baillon), and shui shan (Metasequoia glyptostroboides Hu and W. C. Cheng) (Zhang et al 2005). The reserve is part of the Qionglai Mountain range, which is the southeastern edge of the global distribution of snow leopards (Lu et al 2019). The snow leopard was first detected in Wolong by infrared camera traps in 2009 (Qiao et al 2017), and thus research into snow leopards there has only begun relatively recently.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation